2014
DOI: 10.4012/dmj.2013-287
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and morphology of resin composites polished with two-step polishing systems

Abstract: The purpose of this study was to investigate surface roughness (Ra) and morphology of supra-nanofilled [Estelite Omega (EO), Estelite ∑ Quick (EQ)], micro-hybrid [Esthet.X HD (EHD), G-aenial (GAE)] and nano-hybrid [Clearfil Majesty Posterior (CMP), Charisma Diamond (CD), Beautifil II (BII)] composites polished with two-step polishing systems [Enhance/PoGo (EP); Venus Supra (VS)]. Composite discs, 30 of each type, were prepared. Each composite group was divided into three subgroups: Mylar (control), EP and VS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 31 publications
(64 reference statements)
1
37
0
Order By: Relevance
“…In a study by Endo and colleagues, the polishing effect of the Venus Supra polisher on several nano‐hybrid composites was evaluated with SEM and it was observed that there were some dislodged large filler particles along with superficial grinding scratches from the polisher. Say and colleagues also reported resin removal along with some filler debonding with the Venus Supra on a nano‐hybrid composite.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a study by Endo and colleagues, the polishing effect of the Venus Supra polisher on several nano‐hybrid composites was evaluated with SEM and it was observed that there were some dislodged large filler particles along with superficial grinding scratches from the polisher. Say and colleagues also reported resin removal along with some filler debonding with the Venus Supra on a nano‐hybrid composite.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have shown that the smoothest surface is obtained when the resin composite is polymerized against a Mylar strip . Even though the highest quality of smoothness is obtained, due to the low mechanical properties of this outer layer and the need for contouring and adjusting the occlusion, further F/P procedures are always necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1516] Hardness of material is defined as its resistance to permanent surface indentation or penetration, and this property is related to material strength, ductility, elastic stiffness, plasticity, strain, toughness, viscoelasticity, and viscosity. [1718]…”
Section: Discussionmentioning
confidence: 99%
“…In addition to displaying good physical properties, RBC restorations should be esthetically pleasing and smooth to reduce the accumulation of plaque. Consequently, the surface roughness after simulated masticatory and toothbrush wear is an important feature to consider when determining which RBC is best to use in a restoration . In a systematic review to determine if nanofill or submicron RBCs were smoother and retained their surface gloss after toothbrushing compared with micro‐hybrid RBCs, it was reported that there was no good evidence to support the use of nanofill or submicron RBCs compared with microhybrid filled RBCs .…”
Section: Introductionmentioning
confidence: 99%